PSYCHOLOGICAL TYPE OF RESPONSE AMONG PATIENTS WITH CORONARY HEART DISEASE AFTER HAVING BYPASS SURGERY AND STENTING OF CORONARY ARTERIES - Azatyan, N.G. (Modern Psychology, 2020)
The aim of our study was to discover the nature of psychological response of patients with coronary heart disease in the following two groups: after having bypass surgery and stenting of coronary arteries. In both mentioned groups there are common types of response such as: neurasthenic, apathic, hypochondriac and anxious. Based on our finding we concluded that the strategy of psychological intervention and correction preferably focuses on the change of perception of the illness and personal growth of the patients, including raise of self-awareness and creation of constructive ways to responses of coronary heart disease.